Normalisation des compétences et rationalisation pédagogique. Le cas de la formation technique au Québec - Sylvie Monchatre (Recherches en Éducation)
Education policies tend, more and more, to refer to efficiency. Therefore, new public management is set up to develop school autonomy, contract-based links between schools and the state, and evaluation. But we assume that the search for efficiency also entails pedagogical rationalization, in order to change the cognitive contents of courses and the way of teaching. In this paper, we discuss this hypothesis about the case of the Quebecer “Renouveau collegial” (colleges renewal) carried out in 1993, and in the course of which “competency-based training” was implemented for curriculum building. The example of technical education shows that this reform leads to normalization of competencies, which does not fall within the renewal of learning theories but responds to market requirements, more than giving any teaching tools.